Biointeractions of nanomaterials - Sutariya, Vijaykumar B.; Pathak, Yashwant (CRC Press, Taylor & Francis Group, 2015)
"The purpose of this book is to focus on the biointeraction of nanomaterials, an area that has not been previously addressed in detail. It also covers various techniques and tests that have been developed to evaluate the toxicity of materials at the nano level. The interactions of nanomaterials and nanosystems within biosystems are a concern for the scientific community. This book is targeted toward academic researchers as well as industry members who are involved in the development of nanosystems. Many graduate schools have initiated courses in nanotechnology and applications. This book will be a great resource for students as well as professors. Additionally, this will be a useful tool for industrial scientists investigating technology to update their nanotoxicology and nano-safety understanding. The objective of the book is to address issues related to toxicity and safety of nanomaterials and nanosystems. It also covers the interactions of these in biological systems, various tools and methods used to evaluate the toxicity and safety issues. The volume comprises 20 chapters written by leading scientists in the field of nanotechnology. Chapter 1 covers the challenges and solutions of bio interactions of nanomaterials. This is followed by three chapters that address the assessment and characterization of nanosystems in the bio-environment"--Resumé vydavatele